Knowledge and Attitudes about Antibiotics and Antibiotic Resistance of 2404 UK Healthcare Workers - Diane Ashiru-Oredope; Ella Casale; Eleanor Harvey; Eno Umoh; Sagar Vasandani; Jacqui Reilly; Susan Hopkins (MDPI AG, 2022)
Background: Using the COM-B model as a framework, an EU-wide survey aimed to ascertain multidisciplinary healthcare workers' (HCWs') knowledge, attitudes and behaviours towards antibiotics, antibiotic use and antibiotic resistance. The UK findings are presented here. Methods: A 43-item questionnaire was developed through a two-round modified Delphi consensus process. The UK target quota was 1315 respondents. Results: In total, 2404 participants responded. The highest proportion were nursing and midwifery professionals (42%), pharmacists (23%) and medical doctors (18%). HCWs correctly answered that antibiotics are not effective against viruses (97%), they have associated side effects (97%), unnecessary use makes antibiotics ineffective (97%) and healthy people can carry antibiotic-resistant bacteria (90%). However, fewer than 80% correctly answered that using antibiotics increases a patient's risk of antimicrobial resistant infection or that resistant bacteria can spread from person to person. Whilst the majority of HCWs (81%) agreed there is a connection between their antibiotic prescribing behaviour and the spread of antibiotic-resistant bacteria, only 64% felt that they have a key role in controlling antibiotic resistance. The top three barriers to providing advice or resources were lack of resources (19%), insufficient time (11%) and the patient being uninterested in the information (7%). Approximately 35% of UK respondents who were prescribers prescribed an antibiotic at least once in the previous week to responding to the survey due to a fear of patient deterioration or complications. Conclusion: These findings highlight that a multifaceted approach to tackling the barriers to prudent antibiotic use in the UK is required and provides evidence for guiding targeted policy, intervention development and future research. Education and training should focus on patient communication, information on spreading resistant bacteria and increased risk for individuals.